ANALISIS PRAKTIK JUAL BELI KARET DI DESA KAYU LAUT KECAMATAN PANYABUNGAN SELATAN DALAM PERSPEKTIF EKONOMI ISLAM - Jureid (EKSYA : Jurnal Ekonomi Syariah, 2022)
Buying and selling is a transaction carried out by both parties, namely the seller and the buyer in terms of transferring ownership rights to an object which is preceded by a contract and delivery of a predetermined amount of money. This study aims to find out how the practice of buying and selling rubber latex in the Kayu Selatan Village of Panyabungan, and how its status is reviewed according to Islamic law. The research method used is a field research method, and the nature of the research is descriptive qualitative and juridical. Sources of data collected are primary data and secondary data. The data collection is by using, interviews, observation and documentation. The result of the research is that the practice of buying and selling rubber sap in Kayu Laut village occurs in several stages, namely: first, rubber farmers harvest, usually every week on weekends (Tuesday) and sell it to a rubber sap agent or Toke, Toke will weigh the sap that has been harvested, after the sap is weighed in a sack or hanging scale. The buying and selling of rubber in Kayu Laut Village occurs normally. However, in practice there are deviations that occur, namely cutting the scales by 1 kg every 20 Kg. This is done as an anticipation of losses due to shrinkage of the sap after drying. In addition, there are deviations in the form of adding particles by Penderes as an effort to get more profit and anticipating the cuts made by Toke. In addition, there was also an abnormal weighing, the sap being weighed was still shaking but it had been calculated by the toke. This abnormal scale is also the reason for Penderes adding particles to their sap. The practice of cutting the scales, adding particles and weighing scales that are calculated when shaking is a practice that is not in accordance with Islamic law. This clearly violates the terms of sale and purchase on the object of buying and selling and attitudes on the subject of buying and selling. In addition, there are also dishonest, untrustworthy attitudes, categories of giyas and tathfif which are strictly prohibited in Islamic law.